Comparative Study of Regulations, Governance, Management, and Innovation Models in the Development of Muhammadiyah Waqf with Malaysia and Brunei Darussalam - Arin Setiyowati; Nisful Laila; Raditya Sukmana; Salma Nadia Salsabilla (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
This study presents a comparative analysis of waqf regulation, governance, management, and innovation in Muhammadiyah (Indonesia), Malaysia, and Brunei Darussalam. The aim is to identify similarities and differences in their waqf systems and evaluate how governance and innovation impact community welfare. A qualitative library research approach was used, focusing on waqf-related regulations, management structures, and asset development strategies. Muhammadiyah manages waqf independently through internal institutional policies, guided by Law No. 41 of 2004. In Malaysia, waqf is regulated by the State Islamic Religious Councils (Majlis Agama Islam Negeri, MAIN), which promote corporate-based management such as property development and Sharia-compliant investments, exemplified by the Selangor Waqf Corporation (Perbadanan Wakaf Selangor, PWS). Brunei Darussalam centralizes waqf under the Ministry of Religious Affairs (Kementerian Hal Ehwal Ugama, KHEU), with strict regulations and strong state support for Islamic economic empowerment. In terms of innovation, Malaysia demonstrates a more advanced corporate waqf model with productive asset management, while Brunei prioritizes centralized stability. Muhammadiyah continues to adopt new models such as cash waqf and Islamic investments, though improvement is still needed in professional asset governance and transparency. This research introduces a novel comparative framework by analyzing multi-country waqf governance and applying the concept of Good Waqf Governance, including transparency, accountability, and efficiency. Unlike previous studies that examined isolated cases, this paper maps cross-national governance strategies and their socio-economic outcomes. Furthermore, it highlights Malaysia’s and Brunei’s potential as models for Muhammadiyah’s reform. One key recommendation is to integrate Malaysia’s corporate waqf framework into Muhammadiyah’s waqf strategy to enhance long-term sustainability and economic returns. The study contributes to the discourse on Islamic philanthropy by offering scalable strategies for revitalizing waqf institutions in the Muslim world.